THE ROLE OF INFORMATION CREDIBILITY IN EWOM ON SOCIAL MEDIA TOWARD ONLINE PURCHASE INTENTION OF BOYCOTTED AMERICAN PRODUCTS: A CASE STUDY ON GEN Z - Azhari, Aprillia Dwi; Kholif, Ulfia Dwi Nur; Leonita, Lily (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Social media is becoming a crucial digital information ecosystem, with electronic word of mouth (eWOM) significantly influencing consumer decisions. eWOM spreads information quickly to a wide audience, facilitating product comparison, but poses challenges in distinguishing credible information. This study aims to analyze the role of information credibility, attitude towards information, and eWOM in influencing online purchase intention of boycotted American products. Using quantitative research methods and an associative approach, data was collected through an online survey of 200 gen Z consumers, who are individuals aged 12-27 years old, active users of social media, and have knowledge of the boycott. Data analysis was carried out using the PLS-SEM technique with SmartPLS software. The results showed that information credibility positively affects information usefulness, online purchase intention, and information adoption. Information usefulness contributes positively to attitude and adoption, although it is not significant to online purchase intention. Attitude towards information has a positive effect on adoption, but not on purchase intention. This research emphasizes the importance of credibility and information usefulness in influencing attitudes and adoption, although not all relationships contribute directly to online purchase intentions.